Beyond Contributory Pensions : Fourteen Experiences with Coverage Expansion in Latin America - Rofman, Rafael; Apella, Ignacio; Vezza, Evelyn (Washington, DC: World Bank, 2014)
Latin America's population is aging, and many among the growing elderly population are not protected by traditional pension schemes. In response, policy makers have been reevaluating their income protection systems so that between 2000 and 2013, the majority of Latin American countries reformed their social pension schemes to provide near-universal coverage for the elderly. Before this unprecedented wave of reform, most income protection in Latin America was provided through contributory pensions available only to formal sector workers. Considering that informal and unpaid employment characterize labor force participation throughout the region, many elderly were left vulnerable to poverty. The new noncontributory pension programs have alleviated this risk. But countries are still evaluating how to best balance the need for inclusivity with the need for fiscal sustainability. This report examines recent reforms in Argentina, Bolivia, Brazil, Chile, Colombia, Costa Rica, Ecuador, El Salvador, Mexico, Panama, Paraguay, Peru, Trinidad and Tobago, and Uruguay. All countries share the goal of comprehensive pension coverage, but each has unique political environments, social conditions, and economic capacities. Design and implementation of coverage expansion, consequently, has diverged. Comparing results across the region reveals which policies have yielded the most equitable and sustainable outcomes. Each chapter includes a comprehensive analysis of a country's reform experience: a description of significant political and economic developments, the challenges of implementing income protection policies, and prospects for the reforms' durability over time. This report represents a significant addition to the literature on income protection for the elderly.